Enhanced Solubility of Anti-HER2 scFv Using Bacterial Pelb Leader Sequence: Influence of leader sequence on anti-HRR2 scFv expression - Farshdari, Farzaneh; Ahmadzadeh, Maryam; Jahandar, Hoda; Mohit, Elham (Iranian Journal of Pharmaceutical Sciences, 2019)
Single chain Fragment variable (scFv) is an antibody fragment consisting variable regions of heavy and light chains. scFvs enhance their penetrability into tissues while maintaining specific affinity and having low immunogenicity. Insoluble inclusion bodies are formed when scFvs are expressed in reducing bacterial cytoplasm. One strategy for obtaining functionally active scFv is to translocate the scFv into the oxidized environment of the periplasm where the possibility for disulfide bond formation is increased. This can be achieved by cloning the gene in a vector containing N-terminal pelB leader peptide that exports foreign proteins to the periplasmic space. The aim of this study is to evaluate the influence of periplasmic localization using pelB leader peptide on the solubility of anti-HER2 scFv. Herein, anti-HER2 scFv gene was cloned between NcoI and XhoI sites of pET-22b (+) containing pelB leader peptide and in the same sites of pET-28b (+) (without pelB). The expression in BL21 (DE3) was induced using IPTG and was analyzed using SDS-PAGE and Western blot experiment. Then, the solubility of anti-HER2 scFv in BL21 (DE3) containing both pET-22 and pET-28 (anti-HER2 scFv) was determined. The results of the present study demonstrated that anti-HER2 scFv was expressed by both pET-22b (+) (+) and pET-28b (+) vectors in BL21 (DE3). The proper expression of anti-HER2 scFv was confirmed by appearance of a 28 kDa band in Western blot analysis. The most anti-HER2 scFv expression from BL21 containing pET-28 (anti-HER2 scFv) was achieved when it was induced by 0.25 mM IPTG at 37 ᵒC, 24 h post-induction. The ratio of soluble/insoluble anti-HER2 scFv was significantly higher in BL21 containing pET22-(anti-HER2 scFv) than in that containing pET-28 (anti-HER2 scFv). Totally, the fusion of pelB signal sequence to anti-HER2 scFv resulted in solubility enhancement. Therefore, the production of functional anti-HER2 scFv with proper disulfide bond can be achieved by directing the recombinant protein to periplasmic space using pelB signal peptide in pET-22b (+) vector.